Sexual Dimorphism in Lesion Size and Sensorimotor Responses Following Spinal Cord Injury - Osimanjiang, Wupu; Allgood, JuliAnne E.; Van Sandt, Rae L.; Burns, Daniel T.; Bushman, Jared S. (Frontiers in Neurology, 2022)
Spinal cord injury (SCI) is a devastating disorder, which impacts the lives of millions of people worldwide with no clinically standardized treatment. Both pro-recovery and anti-recovery factors contribute to the overall outcome after the initial SCI. Sex is emerging as an important variable, which can affect recovery post-SCI. Contusion SCI at T10 was generated in male and female rats. Open-field Basso, Beattie, Bresnahan (BBB) behavioral test, Von Frey test, and CatWalk gate analysis were performed. Histological analysis was performed at the 45-day post-SCI end point. Male/female differences in sensorimotor function recovery, lesion size, and the recruitment of immune cells to the lesion area were measured. A group of males with less severe injuries was included to compare the outcomes for severity. Our results show that both sexes with the same injury level plateaued at a similar final score for locomotor function. Males in the less severe injury group recovered faster and plateaued at a higher BBB score compared to the more severe injury group. Von Frey tests show faster recovery of sensory function in females compared to both male groups. All three groups exhibited reduced mechanical response thresholds after SCI. The lesion area was significantly larger in the male group with severe injury than in females, as well as in males of less severe injury. No significant differences in immune cell recruitment were identified when comparing the three groups. The faster sensorimotor recovery and significantly smaller lesion area in females potentially indicate that neuroprotection against the secondary injury is a likely reason for sex-dependent differences in functional outcomes after SCI.